The presence of the family Anostostomatidae (Orthoptera: Ensifera) in Argentina - Zubarán, Gastón E.; Braun, Holger H. (Zootaxa, 2018)
The family Anostostomatidae comprises about 250 known species of robust insects, similar to crickets, which are widely distributed predominantly in the southern hemisphere. They are divided into eight subfamilies, of which five occur in the Neotropics (Cadena-Castañeda & Cortés-Torres 2013). While there are six species described from central and southern Chile (three in each of the genera Cratomelus and Leiomelus), the only published record of the Anostostomatidae for Argentina refers to two old specimens of Apotetamenus clipeatus in the collection of the Muséum National d’Historie Naturelle in Paris (Griffini 1912, Karny 1935, Cadena-Castañeda & Cortés-Torres 2013).